2015
DOI: 10.32607/20758251-2015-7-3-38-47
|View full text |Cite
|
Sign up to set email alerts
|

Injured Nerve Regeneration using Cell-Based Therapies: Current Challenges

Abstract: This paper reviews the recent research progress in the past several years on promoting peripheral nerve recovery using stem and progenitory cells. The emphasis is placed on studies aimed at assessing various stem cells capable of expressing neurotrophic and growth factors and surviving after implantation in the nerve or a conduit. Approaches to improving nerve conduit design are summarized. The contribution of stem cells to axonal regeneration and neural repair is discussed. The side effects associated with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 98 publications
(184 reference statements)
1
17
0
Order By: Relevance
“…Various known cytokines and GFs within platelet α-granules such as transforming GF-β1, platelet-derived GF (PDGF), vascular endothelial GF (VEGF), insulin-like GF-1 (IGF-1), basic fibroblastic GF, and epidermal GF (EGF) have been discussed as being crucial for cell proliferation and differentiation, stimulation of angiogenesis, and scar control in the process of regenerating peripheral nerve structures 28 . The most potent trophic factors secreted by MSCs and used in regenerative therapies are nerve GF (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3, and IGF-1 29 . Furthermore, MSCs produce angiogenic factors such as VEGF and PDGF 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various known cytokines and GFs within platelet α-granules such as transforming GF-β1, platelet-derived GF (PDGF), vascular endothelial GF (VEGF), insulin-like GF-1 (IGF-1), basic fibroblastic GF, and epidermal GF (EGF) have been discussed as being crucial for cell proliferation and differentiation, stimulation of angiogenesis, and scar control in the process of regenerating peripheral nerve structures 28 . The most potent trophic factors secreted by MSCs and used in regenerative therapies are nerve GF (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3, and IGF-1 29 . Furthermore, MSCs produce angiogenic factors such as VEGF and PDGF 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The most potent trophic factors secreted by MSCs and used in regenerative therapies are nerve GF (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3, and IGF-1 29 . Furthermore, MSCs produce angiogenic factors such as VEGF and PDGF 29 . There is convincing evidence that ADSCs release the BDNF and promote axonal regeneration 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell transplantation by nerve conduits can be used effectively to promote axonal regeneration (Jiang, Jones, & Jia, ). Some factors in determining successful outcomes of cell therapy on nerve regeneration are production of ECM proteins and trophic factors creating a favorable environment for axonal outgrowth, stimulation of angiogenesis, differentiation into SC lineage, facilitation of myelination of regenerating axons, immunosupression in the damaged nerve, and stimulation of differentiation and proliferation of endogenous cells (Petrova, ).…”
Section: Transplantation Of Cell‐seeded Nerve Conduits For Peripheralmentioning
confidence: 99%
“…1). In research conducted on different types of animals, it has been found that the introduction of bone marrow MSCs into the nerve or conduit connecting the ends of a damaged nerve promotes the regeneration of nerve fibers (review: Petrova, 2015). However, the mechanisms of this effect are poorly understood.…”
Section: Discussionmentioning
confidence: 99%